Collectible Investments for the High Net Worth Investor - Satchell, Stephen (Elsevier, 2011)
Many high net worth individuals are interested in diversifying their portfolios and investing in collectibles. A collectible is any physical asset that appreciates in value over time because it is rare or desired by many. Stamps, coins, fine art, antiques, books, and wine are examples of collectibles. Where does the financial advisor or investment manager for these high net worth individuals go to learn about these investments? There is no comprehensive resource from the financial standpoint--until now. Dr Stephen Satchell of Trinity College, Cambridge, has developed a book in which experts in various types of collectibles analyze the financial aspects of investing in these collectibles. Chapters address issues such as: liquidity challenges, tax ramifications, appreciation timelines, the challenge of forecasting and measuring appreciation, and the psychological component of collecting and the role of emotion in collectible investing.